KEBIJAKAN MITIGASI PERUBAHAN IKLIM SEKTOR KEHUTANAN MENYONGSONG RPJMN 2015-2019 DI PROVINSI PAPUA DAN PROVINSI ACEH - Hariyadi Hariyadi (Sekretariat Jenderal DPR RI, 2015)
Having huge tropical forest resources and simultaneously still struggling to cope with the dwindling forest resources, Indonesia’s forest mitigation efforts are very crucial following the agenda of the 2015-2019 mid-term national development planning (the RPJMN). For the government, these become more crucial because of the weak implementation of forestry sector governance, indicated by significant deforestation and forest degradation, extreme forest fires, high tenurial conflicts and land-use and land cover changes. The relevance of these issues is not only related to the recent weak forestry management but also how a set of mid- and long-term national forestry policies can be sustainably implemented. Furthermore, the implementation agenda of climate change mitigation policies of the forestry sector will closely relate to the regional roles. Therefore, putting climate change mitigation policies of the forestry sector in the RPJMN in the framework of the regional roles becomes high priority. The research, applying descriptive analytical approach and considering views from considerablepublic and private stakeholders in the provinces of Papua and Aceh, found that the two provinces have not demonstrated an optimum role in sustaining the national policies. Government’s political will still needs to be directed to more transparent regional roles on this issue. There is also an urgent need to strengthen coordination and synergy between the central and regional government, and efforts to attract more public supports.